Global warming and technical change: Multiple steady-states and policy options - Anton Bondarev; Alfred Greiner (University of Basel, Center of Business and Economics (WWZ), 2018)
In this paper we develop an economic growth model that includes anthropogenic climate change. We include a publicly funded research sector that creates new technologies and simultaneously expands the productivities of existing technologies. The environment is affected by R&D activities both negatively, through the increase of output from productivity growth, as well as positively as new technologies are less harmful for the environment. We find that there may exist two different steadystates of the economy, depending on the amount of research spending: one with less new technologies being developed and the other with more technologies. Thus, a lock-in effect may arise that, however, can be overcome by raising R&D spending sufficiently such that the steady-state becomes unique. We derive the combinations of fiscal policy instruments for which that can be achieved and we study the implications for the economy and for the environment. In particular, the double dividend hypothesis may hold only under some specific conditions
Keywords: C61; C62; O38; O44; Q54; Q58; 330; climate change; doubly-differentiated R&D; double dividend; fiscal policy instruments; technology lock-in